Journeys out of homelessness : the voices of lived experience - Rife, Jamie; Burnes, Donald W. (Boulder, London : Lynne Rienner Publishers, Inc., 2020)
"How do individuals move from being homeless to finding safe, stable, and secure places to live? Can we recreate the conditions that helped them most? What policies are needed to support what worked-and to remove common obstacles? Addressing these questions, Jamie Rife and Donald Burnes start from the premise that the most important voices in efforts to end homelessness are the ones most often missing from the discussion: the voices of those with lived experience. In Journeys Out of Homelessness, they gather the first-person stories of some who have not only survived, but thrived, going on to find positive home situations. Highlighting what we can learn from these personal stories, Rife and Burnes combine them with in-depth discussions of key themes and issues and point to the shifts necessary in current policy and practice that are essential if we are to effectively respond to a problem that has reached epic proportions"--
Includes bibliographical references (pahes 187-194) and index.
Keywords: Homelessness -- United States -- Case studies; Homeless persons -- United States -- Case studies